Principles and Design of Curriculum Development - Nurhikmah, Nurhikmah (NUSANTARA: Jurnal Sains Sosial dan Humaniora, 2025)
This study aims to explore the key principles and design of curriculum development in Madrasah Ibtidaiyah (MI). In the context of Islamic education, the curriculum plays a strategic role in shaping the character of students in accordance with Islamic values. This research employs a qualitative approach with a descriptive method, combining library research and field studies. Data were collected through in-depth interviews, observations, and documentation in several MI institutions. The findings reveal that the principles of curriculum development in MI emphasize relevance, continuity, flexibility, and the integration of Islamic values. Additionally, the curriculum design reflects an adaptation to the Merdeka Curriculum, with a focus on strengthening character education. This study recommends enhancing collaboration among the government, educators, and the community to design a curriculum that is responsive to students' needs and contemporary developments.